Research on the relationship between new business talents' ability and its thinking mode in the era of big data. Issue 1 (January 2021) - Qu, Ying; An, Ruoyu
Abstract: In the era of big data, the development of "new business" really needs talents who use new ways of thinking to solve economic management problems.Therefore, it is very important to comprehensively analyze the relationship between the ability of new business talents and the way of thinking in the era of big data.Through combing the literature, we have collected and sorted out the thinking mode in the era of big data and the ability requirements of new business for talents. This article selects 9 ability elements, including 4 ways of thinking and 5 talent abilities, to present the structural model of the relationship between the ability of new business talents and their thinking mode in the era of big data. Analyzing the relationship between talent abilities and thinking styles from a new perspective of big data, supplementing and expanding the existing research on new business talent's abilities, is conducive to the update of training programs, and has certain significance for integrating teaching resources and optimizing curriculum structure.